A heterogeneous nano copper catalyst and its preparation method and application
By using heterogeneous nanocopper catalysts, the problems of low fluorescence intensity and slow synthesis efficiency of fluorescence dyes in the prior art are solved, and high fluorescence intensity and high efficiency fluorescence dye synthesis are achieved.
Patent Information
- Application Number
- CN202310775652.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-06-28
AI Technical Summary
Existing catalysts are used for the synthesis of fluorescent dyes, with low fluorescence intensity and slow synthesis efficiency.
A heterogeneous nano-copper catalyst is used, which is prepared by mixing, drying and calcining the Cu-EDTA complexing solution and carbide kapok fibers. The modified kapok fibers are used as a support to stably support metal copper ions.
The fluorescence intensity of fluorescent dyes is improved and the synthesis efficiency is significantly improved.
Smart Images

Figure CN116764664B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fluorescent dyes, and in particular to a heterogeneous nano copper catalyst and a preparation method and application thereof. Background Art
[0002] At present, fluorescent dyes are a branch of dyes. In recent decades, they have been widely used in materials, biology, medicine, solar energy utilization and other fields, becoming a key basic research direction in dye chemistry. Fluorescent dyes are widely used in biomolecule labeling, tracking biomolecules in a WYSIWYG manner, and playing a role in studying the location of functional biomolecules. The light intensity and photostability of fluorescent dyes are the primary factors affecting imaging quality, especially the rapid development of single-molecule fluorescence imaging supported by ultra-high resolution technology, which has put forward higher requirements on the light intensity and photostability of fluorescent dyes.
[0003] The synthesis of fluorescent dyes requires a catalyst, but the fluorescent dyes synthesized by existing catalysts have low fluorescence intensity and low synthesis efficiency. Summary of the invention
[0004] The present invention provides a heterogeneous nano copper catalyst and a preparation method and application thereof, which are used to solve the technical problems that fluorescent dyes synthesized by existing catalysts have low fluorescence intensity and slow synthesis efficiency.
[0005] The present invention provides a heterogeneous nano copper catalyst, which is prepared by mixing, drying and calcining a Cu-EDTA complex solution and carbonized kapok fibers;
[0006] The carbonized kapok fiber is formed by calcining modified kapok fiber, and the modified kapok fiber is formed by modifying kapok fiber by using an alkali solution.
[0007] Preferably, the Cu-EDTA complex solution is formed by mixing disodium ethylenediaminetetraacetate EDTA-2Na and copper nitrate hexahydrate Cu(NO3)·6H2O.
[0008] A method for preparing a heterogeneous nano copper catalyst comprises:
[0009] S11: washing and drying the kapok fibers, soaking the dried kapok fibers in an alkaline solution, washing and drying to obtain modified kapok fibers;
[0010] S21: calcining the modified kapok fiber under protective gas conditions to obtain carbonized kapok fiber;
[0011] S31: adding the carbonized kapok fiber to the Cu-EDTA complex solution, mixing, drying to obtain a mixture, and calcining the mixture to obtain a heterogeneous nano-copper catalyst.
[0012] It should be noted that the carbonized kapok fiber is added to the prepared Cu-EDTA complex solution, stirred at room temperature, and then heated and stirred to remove the solvent (water) in the Cu-EDTA complex solution to obtain kapok fiber adsorbed with complex copper, which is then dried to obtain a mixture;
[0013] The mixture is calcined in an inert gas atmosphere to thermally decompose the ligand skeleton in the complex copper solution to obtain a heterogeneous nano-copper catalyst with KF as a carrier. The calcined KF maintains its original structure.
[0014] Preferably, before S31, the method further includes:
[0015] S30: Disodium ethylenediaminetetraacetate EDTA-2Na, copper nitrate hexahydrate Cu(NO3)·6H2O and water are mixed, and NaOH is added to adjust the pH to 6-7 to obtain a Cu-EDTA complex solution.
[0016] Preferably, the molar ratio of Cu:EDTA in the Cu-EDTA complex solution is 1:(1-4).
[0017] Preferably, the alkaline solution is NaOH or NaClO2;
[0018] The concentration of the alkaline solution is 1-10 g / L.
[0019] It should be noted that 1 to 10 g of chemical alkali is dissolved in 1 L of deionized water to obtain an alkali solution with a concentration of 1 to 10 g / L.
[0020] Preferably, the initial calcination temperature in S21 and S31 is 20-30°C, and the heating rate is 5°C / min, and the temperature is raised to 500-900°C.
[0021] Preferably, the protective gas is Ar or N2, and the purity is 99.99% or above.
[0022] Preferably, in said S11, the amount of kapok fiber used is 5 to 50 g;
[0023] In S11, the kapok fiber is washed and then dried, specifically: the kapok fiber is washed and then dried with 2L of water and ethanol, the water is deionized water, and the purity of the ethanol is 99.7% or more;
[0024] In the step S11, the drying temperature is 20 to 100°C.
[0025] Preferably, the copper loading range of the heterogeneous nano-copper catalyst is 0.1 wt% to 20 wt%.
[0026] The use of the above-mentioned heterogeneous nano-copper catalyst or the heterogeneous nano-copper catalyst prepared by the above-mentioned preparation method in the preparation of fluorescent dyes includes:
[0027] S1: mixing the heterogeneous nano-copper catalyst and β-naphthol in a solvent, and introducing oxygen to obtain an intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione;
[0028] S2: mixing the intermediate, ammonium acetate and glacial acetic acid, heating, and condensing and refluxing to obtain a fluorescent dye.
[0029] Preferably, the solvent is selected from one of N,N-dimethylformamide (DMF), methanol, ethanol, tetrahydrofuran (THF) and acetonitrile.
[0030] Preferably, the S1 is specifically:
[0031] Under the condition of 50-100° C., the heterogeneous nano-copper catalyst and β-naphthol are mixed in a solvent, oxygen is introduced to a pressure of 0.1-0.4 MPa, and after stirring, an intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione is obtained;
[0032] The stirring rate is 400-600 r / min.
[0033] Preferably, S2 is specifically:
[0034] The heating temperature is 100-130° C., and the heating time is 4-8 hours.
[0035] Preferably, in S1, the amount of β-naphthol is 0.2-20 mmol, and the purity of β-naphthol is 95% or more;
[0036] In S1, the amount of the catalyst is 20 to 2000 mg;
[0037] In S1, the amount of the solvent is 3 to 300 ml;
[0038] In S2, the amount of ammonium acetate is 1 to 100 mmol;
[0039] In S2, the amount of glacial acetic acid used is 20-150 ml.
[0040] The present invention provides a heterogeneous nano-copper catalyst having the following advantages:
[0041] The carbonized kapok fiber is prepared by mixing, drying and calcining a Cu-EDTA complex solution and carbonized kapok fiber; the carbonized kapok fiber is prepared by calcining modified kapok fiber, and the modified kapok fiber is prepared by modifying kapok fiber by using an alkali solution.
[0042] The invention uses an alkaline solution to modify kapok fibers, thereby removing components such as lignin, hemicellulose, wax and grease on the surface of the kapok fibers, so that the kapok fibers can absorb more metal ions and combine with the metal ions more stably; the modified kapok fibers are then calcined to obtain carbonized kapok fibers, and the carbonized kapok fibers and a Cu-EDTA complexing solution are mixed, dried and calcined to obtain a heterogeneous nano copper catalyst using the kapok fibers as a carrier. The fluorescent dye synthesized using the catalyst has higher fluorescence intensity and higher synthesis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0044] Figure 1 This is a scanning electron microscope image of the 2.0wt% Cu-N-KF catalyst prepared in Example 3 of the present invention;
[0045] Figure 2 XRD characterization of the 2.0wt% Cu-N-KF catalyst prepared in Example 3 of the present invention;
[0046] Figure 3 This is a scanning electron microscope image of the carbonized kapok fiber in step S2 of the method for preparing the heterogeneous nano-copper catalyst in Example 3 of the present invention;
[0047] Figure 4 The synthetic route of the fluorescent dye of Application Example 1 of the present invention;
[0048] Figure 5 The hydrogen spectrum of the fluorescent dye intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione of Application Example 1 of the present invention;
[0049] Figure 6 The high performance liquid chromatogram of the fluorescent dye intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione of Application Example 1 of the present invention;
[0050] Figure 7 This is a single crystal image of the fluorescent dye of Application Example 1 of the present invention;
[0051] Figure 8 This is a real picture of the fluorescent dye of Application Example 1 of the present invention. DETAILED DESCRIPTION
[0052] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] The present invention provides a heterogeneous nano copper catalyst and a preparation method and application thereof, which are used to solve the technical problems that fluorescent dyes synthesized by existing catalysts have low fluorescence intensity and slow synthesis efficiency.
[0054] Most fluorescent dyes are organic molecules with multiple aromatic rings, containing specific groups, such as fluorescent emitting groups: carbonyl, nitrogen-nitrogen double bond, carbon-nitrogen double bond, etc., auxochromic groups: primary amine, secondary amine, hydroxyl, ether bond, amide, etc. The larger the intramolecular conjugated system, the stronger the planarity and the higher the fluorescence intensity. Some factors that can increase the degree of conjugation can increase the fluorescence efficiency and move the fluorescence wavelength toward the long-wave direction.
[0055] There are abundant and diverse natural plant fiber resources available for development and utilization in nature. Realizing their efficient and full utilization is an important means to alleviate the current global resource shortage and environmental pollution crisis that has attracted much attention. KF is a natural single-cell fruit fiber with extremely high hollowness. It has a cylindrical appearance in the longitudinal direction, a circular or elliptical cross-section, a smooth surface without significant convolution, a single fiber with closed ends, and an air-filled interior to form an airbag structure. Taking advantage of the characteristics of KF such as hollowness and thin walls, it can be used as a natural polymer substrate or biological template, which has some natural advantages in designing and preparing functional composite materials with unique structures and properties.
[0056] Wherein, the reagents or raw materials used in the following examples are all commercially available or homemade.
[0057] The preparation method of the heterogeneous nano-copper catalyst provided in the embodiment of the present invention comprises:
[0058] Prepare Cu-EDTA complexing solution:
[0059] Mix 0.00629 mmol of disodium ethylenediaminetetraacetate EDTA-2Na, 0.00629 mmol of copper nitrate hexahydrate Cu(NO3)·6H2O and 40 ml of deionized water, add NaOH to adjust the pH to 6-7, and obtain 40 mL, 10 mg / ml Cu-EDTA complex solution (Cu: EDTA = 1:1).
[0060] Example 1
[0061] S11: preparing modified kapok fiber: 10 g of kapok fiber KF was cleaned with 2 L of water and ethanol, dried at 80° C. for 6 h, and the dried 10 g of kapok fiber was immersed in 25% NaClO2 solution (concentration: 8 g / L) at 80° C. for 3 h, then washed with deionized water until neutral, and dried to obtain modified kapok fiber;
[0062] S21: preparing carbonized kapok fiber: placing the modified kapok fiber in a tubular furnace and calcining it under an atmosphere of N2 as a protective gas, the calcination conditions are: initial temperature 20°C, heating rate 5°C / min, heating to 700°C, keeping at 700°C for 2h and then cooling to obtain carbonized kapok fiber, the carbonized kapok fiber is black flocculent fiber, and grinding it into powder;
[0063] S31: Preparation of Cu-N-KF catalyst: Add 100 μl of 10 mg / ml Cu-EDTA complex solution (Cu:EDTA=1:1), 500 mg of carbonized kapok fiber and 20 mL of deionized water into a 50 ml beaker, stir magnetically at room temperature for 1 h, then heat to 100°C, remove the solvent water under magnetic stirring, and after the solvent is evaporated, move the catalyst to a blower dryer and dry at 70°C for 4 h to obtain a mixture; move the mixture to a tubular furnace for calcination, calcination conditions: initial temperature 20°C, heating rate 5°C / min, heat to 700°C, keep at 700°C for 2 h and then cool to obtain 486 mg of black solid powder, and obtain a Cu-N-KF catalyst with a mass percentage of metallic copper of 0.2 wt%.
[0064] Example 2
[0065] S11: preparing modified kapok fiber: 10 g of kapok fiber KF was cleaned with 2 L of water and ethanol, dried at 80° C. for 6 h, and the dried 10 g of kapok fiber was immersed in 25% NaClO2 solution (concentration: 8 g / L) at 80° C. for 3 h, then washed with deionized water until neutral, and dried to obtain modified kapok fiber;
[0066] S21: preparing carbonized kapok fiber: placing the modified kapok fiber in a tubular furnace and calcining it under an atmosphere of N2 as a protective gas, the calcination conditions are: initial temperature 20°C, heating rate 5°C / min, heating to 700°C, keeping at 700°C for 2h and then cooling to obtain carbonized kapok fiber, the carbonized kapok fiber is black flocculent fiber, and grinding it into powder;
[0067] S31: Preparation of Cu-N-KF catalyst: Add 500 μl of 10 mg / ml Cu-EDTA complex solution (Cu:EDTA=1:1), 500 mg of carbonized kapok fiber and 20 mL of deionized water into a 50 ml beaker, stir magnetically at room temperature for 1 h, then heat to 100°C, remove the solvent water under magnetic stirring, and after the solvent is evaporated, move the catalyst to a blower dryer and dry at 70°C for 4 h to obtain a mixture; move the mixture to a tubular furnace for calcination, calcination conditions: initial temperature 20°C, heating rate 5°C / min, heat to 700°C, keep at 700°C for 2 h and then cool to obtain 491 mg of black solid powder, and obtain a Cu-N-KF catalyst with a mass percentage of metallic copper of 1.0 wt%.
[0068] Example 3
[0069] S11: preparing modified kapok fiber: 10 g of kapok fiber KF was cleaned with 2 L of water and ethanol, dried at 80° C. for 6 h, and the dried 10 g of kapok fiber was immersed in 25% NaClO2 solution (concentration: 8 g / L) at 80° C. for 3 h, then washed with deionized water until neutral, and dried to obtain modified kapok fiber;
[0070] S21: preparing carbonized kapok fiber: placing the modified kapok fiber in a tubular furnace and calcining it under an atmosphere of N2 as a protective gas, the calcination conditions are: initial temperature 20°C, heating rate 5°C / min, heating to 700°C, keeping at 700°C for 2h and then cooling to obtain carbonized kapok fiber, the carbonized kapok fiber is black flocculent fiber, and grinding it into powder;
[0071] S31: Preparation of Cu-N-KF catalyst: Add 500 μl of 10 mg / ml Cu-EDTA complex solution (Cu:EDTA=1:1), 500 mg of carbonized kapok fiber and 20 mL of deionized water into a 50 ml beaker, stir magnetically at room temperature for 1 h, then heat to 100°C, remove the solvent water under magnetic stirring, and after the solvent is evaporated, move the catalyst to a blower dryer and dry at 70°C for 4 h to obtain a mixture; move the mixture to a tubular furnace for calcination, calcination conditions: initial temperature 20°C, heating rate 5°C / min, heat to 700°C, keep at 700°C for 2 h and then cool to obtain 490 mg of black solid powder, and obtain a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0 wt%.
[0072] Example 4
[0073] The difference from Example 3 is that the concentration of the NaClO2 solution in S11 is 1 g / L;
[0074] 487 mg of black solid powder was obtained in S31, and a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0 wt% was prepared.
[0075] Example 5
[0076] The difference from Example 3 is that the concentration of the NaClO2 solution in S11 is 10 g / L;
[0077] In S31, 494 mg of black solid powder was obtained, and a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0 wt% was prepared.
[0078] Example 6
[0079] The difference from Example 3 is that the calcination conditions in S21 are: initial temperature 30°C, heating rate 5°C / min, heating to 500°C, keeping at 500°C for 2h and then cooling;
[0080] The calcination conditions in S31 are: initial temperature 30°C, heating rate 5°C / min, heating to 500°C, keeping at 500°C for 2h and then cooling; 498mg of black solid powder is obtained, and a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0wt% is obtained.
[0081] Example 7
[0082] The difference from Example 3 is that the calcination conditions in S21 are: initial temperature 30°C, heating rate 5°C / min, heating to 900°C, keeping at 900°C for 2h and then cooling;
[0083] The calcination conditions in S31 are: initial temperature 30°C, heating rate 5°C / min, heating to 900°C, keeping at 900°C for 2h and then cooling; 478mg of black solid powder is obtained, and a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0wt% is obtained.
[0084] Example 8
[0085] The difference from Example 3 is that the calcination conditions in S21 are: initial temperature 20°C, heating rate 5°C / min, heating to 500°C, keeping at 500°C for 2h and then cooling;
[0086] The calcination conditions in S31 are: initial temperature 20°C, heating rate 5°C / min, heating to 500°C, keeping at 500°C for 2h and then cooling; 499mg of black solid powder is obtained, and a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0wt% is obtained.
[0087] Example 9
[0088] The difference from Example 3 is that the calcination conditions in S21 are: initial temperature 20°C, heating rate 5°C / min, heating to 900°C, keeping at 900°C for 2h and then cooling;
[0089] The calcination conditions in S31 are: initial temperature 20°C, heating rate 5°C / min, heating to 900°C, keeping at 900°C for 2h and then cooling; 476mg of black solid powder is obtained, and a Cu-N-KF catalyst with a mass percentage of metallic copper of 2.0wt% is obtained.
[0090] The method for preparing the catalyst of the present invention is simple and quick, and the hollow structure of the kapok fiber is well preserved. The metal copper ions used can be stably loaded on the kapok fiber KF, and the copper ions are adsorbed in large quantities to reduce toxicity. The catalyst has a good catalytic effect on the preparation and synthesis of fluorescent dyes and is easy to recover.
[0091] The carbonized kapok fibers prepared in Example 3 were observed under an electron microscope. Figure 3 As shown, the kapok fiber at this time is a tubular structure; the 2.0wt% Cu-N-KF catalyst prepared in Example 3 was observed by electron microscope, and the results are as follows Figure 1 As shown, the morphology of the Cu-N-KF catalyst prepared in the present application has not changed substantially, and still presents a tubular structure;
[0092] The 2.0 wt% Cu-N-KF catalyst prepared in Example 3 was characterized by XRD. Figure 2 As shown, from Figure 2 The marked Cu crystal plane shows that the Cu-N-KF catalyst prepared in the present application contains copper.
[0093] Application Example 1
[0094] according to Figure 4 The reaction route of the invention is to apply the 2.0wt% Cu-N-KF catalyst prepared in Example 3 to prepare a fluorescent dye, comprising:
[0095] S1: 800 mg of the prepared 2.0 wt% Cu-N-KF catalyst was weighed into a 40 mL high pressure reactor, 20 mmol of β-naphthol substrate was added and mixed in 20 mL of DMF, the reactor was sealed, O2 was filled into the reactor six times and discharged, all the air in the reactor was discharged, and then O2 was introduced to make the pressure reach 0.3 MPa, and the mixture was stirred at a temperature of 80°C, the stirring rate was 400 r / min, and the reaction time was 12 h to obtain the intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione;
[0096] S2: Add the intermediate product 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione into a round-bottom flask, and then add 100 mmol of ammonium acetate and 150 ml of glacial acetic acid and mix at 120° C. for 4 to 8 hours. After condensation and reflux, a fluorescent dye with blue fluorescence is obtained.
[0097] Application Example 2
[0098] The difference from Application Example 1 is that the stirring rate in S1 is 600 r / min.
[0099] Application Example 3
[0100] The difference from Application Example 1 is that O2 is introduced into S1 to make the pressure reach 0.1 MPa.
[0101] Application Example 4
[0102] The difference from Application Example 1 is that O2 is introduced into S1 to make the pressure reach 0.4 MPa.
[0103] Application Example 5
[0104] The difference from Application Example 1 is that stirring is performed at 50° C. in S1 .
[0105] Application Example 6
[0106] The difference from Application Example 1 is that the stirring is performed at 100° C. in S1 .
[0107] Application Example 7
[0108] The difference from Application Example 1 is that the mixing is performed at 100° C. in S2.
[0109] Application Example 8
[0110] The difference from Application Example 1 is that the mixing is performed at a temperature of 130° C. in S2.
[0111] according to Figure 5 The hydrogen spectrum shown can determine the molecular formula and structure of the intermediate in S1, thus confirming it to be 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione;
[0112] according to Figure 6 As shown, the intermediate is analyzed by high performance liquid chromatography, and the yield of the intermediate of the present invention can reach a relatively high level, and the yield of the intermediate is 20 to 90%;
[0113] according to Figure 7 The single crystal X-ray diffraction shown can determine the crystal structure of the fluorescent dye crystal material, including C, H, N and O elements;
[0114] The fluorescent dye of the present invention is synthesized through the intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione, and the intramolecular conjugated system is relatively large, such as Figure 8 As shown, the fluorescence intensity of the fluorescent dye synthesized by the present invention is relatively high.
[0115] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An application of a heterogeneous nano copper catalyst in the preparation of a fluorescent dye, characterized in that: include: S1: mixing the heterogeneous nano-copper catalyst and β-naphthol in a solvent, and introducing oxygen to obtain an intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione; S2: mixing the intermediate, ammonium acetate and glacial acetic acid, heating, and condensing and refluxing to obtain a fluorescent dye; The heterogeneous nano copper catalyst is prepared by mixing, drying and calcining a Cu-EDTA complex solution and carbonized kapok fibers; The carbonized kapok fiber is formed by calcining modified kapok fiber, and the modified kapok fiber is formed by modifying kapok fiber by using an alkali solution.
2. The use according to claim 1, characterized in that: The Cu-EDTA complex solution is prepared by mixing disodium ethylenediaminetetraacetate EDTA-2Na and copper nitrate hexahydrate Cu(NO3)·6H2O.
3. The use according to claim 1, characterized in that: The solvent is selected from one of N,N-dimethylformamide DMF, methanol, ethanol, tetrahydrofuran THF and acetonitrile.
4. The use according to claim 1, characterized in that: The S1 is specifically: Under the condition of 50-100° C., the heterogeneous nano-copper catalyst and β-naphthol are mixed in a solvent, oxygen is introduced to a pressure of 0.1-0.4 MPa, and after stirring, an intermediate 2'-hydroxy-[1,1'-binaphthyl]-3,4-dione is obtained; The stirring rate is 400-600 r / min.
5. The use according to claim 1, characterized in that: The S2 is specifically: The heating temperature is 100-130° C., and the heating time is 4-8 hours.
6. A method for preparing a heterogeneous nano-copper catalyst, for preparing the heterogeneous nano-copper catalyst according to any one of claims 1 to 5, characterized in that: include: S11: washing and drying the kapok fibers, soaking the dried kapok fibers in an alkaline solution, washing and drying to obtain modified kapok fibers; S21: calcining the modified kapok fiber under protective gas conditions to obtain carbonized kapok fiber; S31: adding the carbonized kapok fiber to the Cu-EDTA complex solution, mixing, drying to obtain a mixture, and calcining the mixture to obtain a heterogeneous nano-copper catalyst.
7. The method for preparing a heterogeneous nano-copper catalyst according to claim 6, characterized in that: Before S31, the method further includes: S30: Disodium ethylenediaminetetraacetate EDTA-2Na, copper nitrate hexahydrate Cu(NO3)·6H2O and water are mixed, and NaOH is added to adjust the pH to 6-7 to obtain a Cu-EDTA complex solution.
8. The method for preparing a heterogeneous nano-copper catalyst according to claim 6, characterized in that: The alkaline solution is NaOH or NaClO2; The concentration of the alkaline solution is 1-10 g / L.
9. The method for preparing a heterogeneous nano-copper catalyst according to claim 6, characterized in that: The initial calcination temperature in S21 and S31 is 20-30°C, and the heating rate is 5°C / min, and the temperature is raised to 500-900°C.
Citation Information
Patent Citations
Heterogeneous nano-copper catalyst as well as preparation method and application thereof
CN113262786A